2012
DOI: 10.1124/jpet.112.193995
|View full text |Cite
|
Sign up to set email alerts
|

Translational Evaluation of JNJ-18038683, a 5-Hydroxytryptamine Type 7 Receptor Antagonist, on Rapid Eye Movement Sleep and in Major Depressive Disorder

Abstract: In rodents 5-hydroxytryptamine type 7 (5-HT 7 ) receptor blockade has been shown to be effective in models of depression and to increase the latency to rapid eye movement (REM) sleep and decrease REM duration. In the clinic, the REM sleep reduction observed with many antidepressants may serve as a biomarker. We report here the preclinical and clinical evaluation of a 5-HT 7 receptor antagonist, (3-(4-chlorophenyl)-1, 4,5,6,7,8-hexahydro-1-(phenylmethyl)pyrazolo [3,4-d]azepine 2-hydroxy-1,2,3-propanetricarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 33 publications
2
84
0
Order By: Relevance
“…Indeed, Monti et al reported that administration of buspirone or ipsapirone, both of which are 5-HT 1A receptor partial agonists, suppresses REM in rats. In addition, the 5-HT 7 receptor antagonists, SB-269970 and JNJ-18038683, have been reported to exhibit REM-suppressive and antidepressant-like effects in animals and humans (12,14,15). Consistent with these findings, our unpublished data show that tandospirone, a 5-HT 1A receptor partial agonist, and SB-258741, a 5-HT 7 receptor antagonist, suppress REM sleep (data not shown).…”
Section: Lurasidone Suppresses Rapid Eye Movement Sleep and Improves supporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, Monti et al reported that administration of buspirone or ipsapirone, both of which are 5-HT 1A receptor partial agonists, suppresses REM in rats. In addition, the 5-HT 7 receptor antagonists, SB-269970 and JNJ-18038683, have been reported to exhibit REM-suppressive and antidepressant-like effects in animals and humans (12,14,15). Consistent with these findings, our unpublished data show that tandospirone, a 5-HT 1A receptor partial agonist, and SB-258741, a 5-HT 7 receptor antagonist, suppress REM sleep (data not shown).…”
Section: Lurasidone Suppresses Rapid Eye Movement Sleep and Improves supporting
confidence: 79%
“…It has been reported that REM sleep increases in the depressive state and that antidepressants ameliorate REM sleep concomitant with depressive symptoms. As some antidepressants also suppress REM sleep even in healthy subjects and naïve animals, it is believed that REM suppression may be a useful biomarker for antidepressant effect (9,10,12). Indeed, paroxetine at a dose of 10 mg/kg significantly decreased REM sleep duration and prolonged REM sleep latency under the current experimental conditions (data not shown).…”
Section: Lurasidone Suppresses Rapid Eye Movement Sleep and Improves mentioning
confidence: 81%
“…[3] Moreover, experiments that involved 5-HT 7 R knockout mice led to observation, that its blockade may reduce immobility effect of animals in forced swim test (FST), making searching for 5-HT 7 R antagonists a promising direction for future depression treatment. [7] Compound SB-269970A (2, Figure 1), another promising and one of the most active and selective 5-HT 7 R antagonists, used very often as a pharmacological tool for 5-HT 7 receptor examination, has been also rejected from further in vivo studies, because of extremely high blood clearance and short in vivo half-life (t 1/2 < 0.5 h). Unfortunately, this double-blind, active, and placebo-controlled clinical trial in patients with depression has failed.…”
Section: Introductionmentioning
confidence: 99%
“…It is the only such agent that has 5‐HT 7 antagonism as its most potent effect. As such, this study offers the only opportunity to evaluate the sleep effects of 5‐HT 7 antagonism other than the prior study of the effects of a selective 5‐HT 7 antagonist on REM sleep in undisturbed healthy volunteers (Bonaventure et al ., ). We found that 5‐HT 7 antagonism does not affect REM or slow‐wave sleep, at least in the phase advance paradigm, and appears to have a potent effect on sleep maintenance without improving sleep onset.…”
Section: Discussionmentioning
confidence: 97%
“…We found that 5‐HT 7 antagonism does not affect REM or slow‐wave sleep, at least in the phase advance paradigm, and appears to have a potent effect on sleep maintenance without improving sleep onset. The finding of an absence of an effect on REM differs from what was reported with the previously studied selective 5‐HT 7 antagonist (Bonaventure et al ., ). However, it should be noted that in the prior study the dosage was selected so as to be equivalent to a dosage that suppressed REM sleep in animals.…”
Section: Discussionmentioning
confidence: 97%